BS EN 4165-012. Aerospace series. Connectors, electrical, rectangular, modular. Operating temperature 175 °C continuous. Part 012. Flange mounting receptacle 2 and 4 modules, series 3. Product standard (5th August 2021) - British Standards Institution
No abstract available